Properties of gold nanostructures sputtered on glass - Siegel, Jakub; Lyutakov, Olexiy; Rybka, Vladimír; Kolská, Zdeňka; Svorčík, Václav (Nanoscale research letters, 2011)
We studied the electrical and optical properties, density, and crystalline structure of Au nanostructures prepared by direct current sputtering on glass. We measured temperature dependence of sheet resistance and current-voltage characteristics and also performed scanning electron microscopy [SEM] analysis of gold nanolayers. It was shown that within the wide range of temperatures, gold nanolayers (<10 nm) exhibit both metal and semiconducting-like type of conductivity. UV/Vis analysis proved the semiconducting characteristic of intrinsic Au clusters. SEM analysis showed the initiatory stadium of gold layer formation to be running over isolated islands. Gold density calculated from the weight and effective thickness of the layers is an increasing function of the layer thickness up to approximately 100 nm. In thin layers deposited on solid surface, a lattice expansion is observed, which is manifested in the increase of the lattice parameter and the decrease of metal density. With increasing layer thickness, the lattice parameter and the density approach the bulk values.